STRATEGI PEMASARAN DAN DAYA SAING PT. TELEKOMUNIKASI SELULER - Ary Wira Andika (Jurnal Manajemen dan Bisnis, 2013)
The title of the study is "Marketing Strategy and Competitiveness PT.Telekomunikasi Selluler (Telkomsel) Denpasar Bali". The purpose of this study was todetermine management strategies PT. Telekomunikasi Selluler (Telkomsel) face theopportunities, threats, strengths and weaknesses in marketing their products and the rightof marketing strategy for PT. Telekomunikasi Selluler (Telkomsel) to face competition,with analysis of the IE Matrix (Internal External) and a SWOT analysis of the strengths(strengths), weakness (weakness), opportunities (opportunities), threats (threats) at PT.Telekomunikasi Selluler (Telkomsel) Denpasar Bali.The research method used is descriptive qualitative research method of analysis, SWOTMatrix, IFAS Matrix (Internal Factors Analysis Summary) and EFAS Matrix (ExternalFactors Analysis Summary).The results were analyzed using matrix after IE indicates that the current PT.Cellular Telecommunications (Telkomsel) Denpasar Bali, can harvest or divestmentstrategy. Using a SWOT matrix shows the right strategy for Telkomsel is the strategy SO(Strengths Opportunities), which utilize all the power to seize and exploit opportunities asmuch as possible. Marketing strategy implemented by Telkomsel Denpasar Bali iscorrectly by using STP strategy (Segmenting, Targeting, Positioning) and 7P marketingmix (Product, Price, Promotion, Place, People, Process and Physical Evidence).Keywords: SWOT Analysis, Analysis of IE, Management Strategy, Marketing Strategy